KONSEP POLITIK ISLAM KULTURAL PERSPEKTIF NURCHOLISH MADJID - Mohammad Taufiq Rahman; Asep Saeful Mimbar (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2018)
This article is about the political thought of Islam Nurcholish Madjid. For most Islamic societies, Nurcholish is the big thinkers who followed pemikiran-pemikirannya. What is discussed here is especially points where Nurcholish makes a political statement-statement is then taken by colleagues in his day and thereafter. The most notable being discussed here is a thought-provoking cultural politics in the era of new order Nurcholish, who then lashed with political thought at the beginning of the Reformation period. Research methods this article is using a qualitative approach, while the nature of this normative and sociological research. This article is the kind of research libraries or commonly called with (library research). This article aims to find out how the concept of political Islam cultural Perspective Nurcholish Madjid. Results or conclusions of the article is that of religious thought, in political thought Nurcholish asserted any necessity of openness, both Muslims and non-Muslims in Indonesia not to happen "the price of death". Each party in the political arena, according to him, Indonesia must continue to do the bargaining and accommodation of interests each for the creation of a common interest